Adult type rhabdomyoma presenting as a parathyroid adenoma. Issue 2 (10th December 2018) - Lee, John P.; Blake Sullivan, Christopher; Bayon, Rodrigo; Shearer, A. Eliot; Robinson, Robert A.
Abstract: Background: Adult‐type rhabdomyoma (ATR) is a rare mesenchymal tumor of skeletal muscle differentiation. Extracardiac ATR occurs most commonly in the head and neck, but do so in a heterogeneous fashion, arising at numerous different locations within this region. Methods: At our institution, we encountered a patient who was diagnosed clinically with parathyroid adenoma based on signs and symptoms of hyperparathyroidism and suggestive radiologic findings. A parathyroidectomy with intraoperative consultation was performed. Results: The frozen section diagnosis was ambiguous and a diagnosis of ATR was only made on permanent section. Conclusion: Awareness of this tumor can prevent incorrect diagnosis and overtreatment intraoperatively. Herein, we describe the clinical history, pathologic findings, and review histologic features of rhabdomyomas.